Depression and Anxiety in Iranian Patients with Behcet’s Disease: A Single Center Experience - Fani, Mohammad Mehdi; Aflaki, Elham; Ebrahimi, Hooman; Safari, Anahita; Ghanizadeh, Sina; Ranjbar, Maryam; Manafi, Alireza; Borhanihaghighi, Afshin (Galen Medical Journal, 2013)
Background: This study was designed to determine and compare the stress, anxiety and depression levels in Behcet’s disease (BD) patients and a control group of normal individuals. Materials and Methods: One-hundred and six patients with BD were selected as cases and controls were 106 age- and sex-matched participants referred to the Shiraz Dental school clinics due to dental problems. We collected the information with 3 validated Farsi questionnaires: Perceived Stress Scale (PSS) for stress, Beck Anxiety Index (BDI) for depression and Beck Depression Index (BAI) for anxiety. Results: Stress, depression and anxiety levels were significantly higher in patients with BD in comparison with the control group (p<0.001). Conclusions: A high level of stress and depression in BD patients is frequent and PSS, BDI and BAI are useful for determining these variations. Finally, we suggest a psychiatrist consultation in all periods of disease treatment.